Femoral Head Diameters and Sex Differentiation in the Northern Zone (Rajshahi) of Bangladesh (TAJ: Journal of Teachers Association, 2009)
This study was aimed to find out the variations of the femoral head diameters in relation to sex in Bangladeshi people. The study was based on 123 paired human femurs (radiological view) of which 52 were male and 71were female. It was observed that the mean vertical and transverse diameters of the head of the male femur were significantly greater than that of female (P